Identification and drug metabolic characterization of four new CYP2C9 variants CYP2C9*72-*75 in the Chinese Han population - Zhao, Fang-Ling; Zhang, Qing; Wang, Shuang-Hu; Hong, Yun; Zhou, Shan; Zhou, Quan; Geng, Pei-Wu; Luo, Qing-Feng; Yang, Jie-Fu; Chen, Hao; Cai, Jian-Ping; Dai, Da-Peng (Frontiers in Pharmacology, 2022)
Cytochrome 2C9 (CYP2C9), one of the most important drug metabolic enzymes in the human hepatic P450 superfamily, is required for the metabolism of 15% of clinical drugs. Similar to other CYP2C family members, CYP2C9 gene has a high genetic polymorphism which can cause significant racial and inter-individual differences in drug metabolic activity. To better understand the genetic distribution pattern of CYP2C9 in the Chinese Han population, 931 individuals were recruited and used for the genotyping in this study. As a result, 7 synonymous and 14 nonsynonymous mutations variations were identified, of which 4 missense variants were designated as new alleles CYP2C9*72, *73, *74 and *75, which can resulting in the amino acid substitutions of A149V, R150C, Q214H and N418T, respectively. When expressed in insect cell microsomes, all four variants exhibited similar comparable protein expression levels relative to that of the wild-type CYP2C9 enzyme. However, drug metabolic activity analysis revealed that these variants exhibited significantly decreased catalytic ability activities toward three CYP2C9 specific probe drugs, as compared with that of the wild-type enzyme. These data indicate that the amino acid substitution in newly designated variants can cause reduced function of the enzyme and its clinical significance still needs further investigation in the future.